Normal mode finite element analysis of aerofoil wing structure with different materials - M. N. A. M., Asri; N. A. Z., Abdullah; M. S. M., Fouzi; M. S. M., Sani (IOP Publishing, 2019)
There are a lot of study regarding on the aircraft components. One of the critical components for an aircraft would be the wings. The wing structure of an aircraft is one of the complex structures of a designed aircraft. This paper is about identifying the modal properties which are the mode shape and the corresponding natural frequencies of the aircraft wing structure. The modal properties of the wing structure would be compared for two different materials applied towards the wing structures which are the aluminium alloy AA-7075-T6 and AA-2024-T3 which currently being widely used by the aircrafts. The study for this aircraft wing structure would be using the approach of finite element analysis (FEA) method. The 3D model is design by using SolidWorks. The modal properties are identified with the help of MSC PATRAN and MSC NASTRAN. The results obtained for both materials for 10 mode shapes are compared and it could be observed that AA-7075-T6 are much lower compared to AA-2024-T3. Hence, from the result, AA-7075-T6 is more suitable to be used for the wing structures.